1995
DOI: 10.1542/peds.96.2.295
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Immunization Status Among Inner-City Latino and African-American Preschoolers

Abstract: Objective. To identify factors associated with undervaccination at 3 months and 24 months among low-income, inner-city Latino and African-American preschool children. Design. Interviews with a representative sample of inner-city families using a cross-sectional, multi-stage, cluster-sample design combined with a replicated quota sampling approach. Setting. South Central and East Los Angeles areas in inner-city Los Angeles. Population. Eight hundred seventeen Latino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Finally, the generational shift in vaccine-hesitancy patterns through the years may explain the differential impact of education and socioeconomic status on vaccine hesitancy. Prior to the measles elimination period, vaccine hesitancy patterns in the 1980s and 1990s were largely unintentional and was associated with poverty and lack of vaccine access [ 155 ], particularly among immigrant families with limited education [ 156 ]. On the other hand, articles in this review were published between 2000 and 2022 and highlighted the positive correlation between vaccine hesitancy, income, education, and NMEs—the timing of which corresponded with greater information availability and access through the internet and social media, which can influence mothers’ decisions on their children’s vaccination status.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the generational shift in vaccine-hesitancy patterns through the years may explain the differential impact of education and socioeconomic status on vaccine hesitancy. Prior to the measles elimination period, vaccine hesitancy patterns in the 1980s and 1990s were largely unintentional and was associated with poverty and lack of vaccine access [ 155 ], particularly among immigrant families with limited education [ 156 ]. On the other hand, articles in this review were published between 2000 and 2022 and highlighted the positive correlation between vaccine hesitancy, income, education, and NMEs—the timing of which corresponded with greater information availability and access through the internet and social media, which can influence mothers’ decisions on their children’s vaccination status.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that through the integrated program of family planning and immunization services, the woman who visited the health facility for family planning services may be able to vaccinate her kid [ 24 ]. According to a study done on African-American and Latino children in inner-city Los Angeles, health insurance was another factor that determined incomplete immunization [ 25 ]. Furthermore, the finding of this study revealed that the availability of health insurance was the determinant of incomplete immunization this was in line with a study conducted in African-American and Latino children in inner-city Los Angeles [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to a study done on African-American and Latino children in inner-city Los Angeles, health insurance was another factor that determined incomplete immunization [ 25 ]. Furthermore, the finding of this study revealed that the availability of health insurance was the determinant of incomplete immunization this was in line with a study conducted in African-American and Latino children in inner-city Los Angeles [ 25 ]. Health insurance coverage makes preventive services like vaccinations and screening programs more accessible [ 26 ].…”
Section: Discussionmentioning
confidence: 99%